The Exoticism of Coastal Nature and The Value of Spirituality in Sendang Lamongan Batik - Angga Fajar Ramadhan; Syakir Syakir; Djuli Djatiprambud; Muhammad Ibnan Syarif (International Conference on Science, Education, and Technology, 2023)
This study aims to reveal the source of inspiration for Sendang Batik craftsmen in utilizing the exotic nature of the coast and the culture of the transitional Islamic period as an idea for the creation of batik crafts, and to examine the function of batik in the socio-cultural environment of coastal communities. This research is a qualitative-interpretative research with a semiotic-cultural approach. Using Charles Sanders Peirce's semiotic theory and Edmund Burke Feldman's function theory as a knife of analysis and as a theoretical basis in understanding the idea of ​​creation and function of Batik Sendang. The research locus is in Sendangduwur Village, Paciran, Lamongan, East Java with the object of Sendang Batik. Data obtained through observation, interviews and documentation. The results showed that Batik Sendang craftsmen took inspiration from the exotic coastal natural environment in the form of crabs, frog capes, palm leaves and limestone hills, as well as the cultural values ​​of the transitional Islamic period in the form of lotus flower reliefs, paduraksa winged arches, singo mengkok and peacocks in Sunan Sendang Duwur Cemetery complex. Sendang batik in the socio-cultural of coastal communities has a function as (1) the expression of craftsmen in channeling their ideas, desires and creativity through batik craft, (2) magical objects that contain spiritual values ​​that are trusted, believed, internalized and used as guidelines by the community, (3) clothing in social life, both used in daily activities, government agencies, education, health, typical Lamongan clothing and parts of other arts.